Analisis pengaruh citra perusahaan dan kualitas layanan terhadap loyalitas pelanggan melalui kepuasan pelanggan - Bambang Bambang; Triyono Arief Wahyudi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
This study aims to find out the effect of corporate image and its service quality to consumer loyalty and its impact on customer satisfaction. This research uses quantitative data with 100 respondents in JaBoDeTaBek. The method used in this research is regression and the colleration of each variable with 2 sub model using SPSS. The result from this study shows that there is a significant effect between corporate image to costumer satisfactory, a significant effect between quality of service to costumer satisfactory, and also a significant effect between costumer satisfactory to costumer loyalty. Therefore, Team Wound, PT XYZ Jakarta and Bekasi needs to perform effective activities and to always up to date periodically so that the costumers are more loyal to use its products.